Hospitalization risk in bipolar disorder patients treated with lurasidone versus other atypical antipsychotics. (1st February 2019) - Ng-Mak, Daisy; Halpern, Rachel; Rajagopalan, Krithika; Loebel, Antony
Abstract: Objective: This observational study compared the risk of hospitalization for patients with bipolar disorder when treated with lurasidone versus other oral atypical antipsychotics. Methods: This US commercial claims analysis (4 April 2010 through 24 September 2014) used the Optum Research Database to identify adult patients with bipolar disorder treated with oral atypical antipsychotics ( N = 11, 132). The first claim for an atypical antipsychotic defined the index date, with pre-index and post-index periods of 180 and 360 days, respectively. Every month of the post-index period was categorized as monotherapy treatment with lurasidone, aripiprazole, olanzapine, quetiapine, risperidone, ziprasidone, no/minimal treatment or other. Starting with the initial month of treatment, the risk of psychiatric or all-cause hospitalization in the subsequent month was examined based on treatment in the current month and pre-index covariates (age, gender, hospitalizations, emergency room visits, diagnoses for anxiety, alcohol abuse, substance abuse, hypertension, type 2 diabetes and obesity) and time-varying versions of the pre-index covariates using a marginal structural model. Results: After controlling for covariates, relative to lurasidone, the odds of psychiatric and all-cause hospitalization, respectively, were 2–3 times higher for olanzapine (odds ratio [OR] = 2.78, CI 1.09, 7.08, p = .032; OR = 3.20, CI 1.24, 8.26, p = .016), quetiapine (OR = 2.80, CI 1.13, 6.95, p = .026; OR = 3.23, CI 1.29, 8.11, p = .013), risperidone (OR = 2.50, CI 1.01, 6.21, p = .048; OR = 2.79, CI 1.11, 7.02, p = .029), aripiprazole (OR = 2.13, CI 0.87, 5.20, p = .097; OR = 2.57, CI 1.04, 6.37, p = .041) and ziprasidone (OR =2.31, CI 0.91, 5.85, p = .079; OR = 2.49, CI 0.97, 6.40, p = .058). Conclusions: In this claims database analysis, lurasidone-treated patients with bipolar disorder had a significantly lower risk of psychiatric hospitalization compared to quetiapine, olanzapine and risperidone, but not aripiprazole or ziprasidone. Lurasidone-treated patients had a significantly lower risk of all-cause hospitalization compared to quetiapine, olanzapine, risperidone and aripiprazole, but not ziprasidone.